Acute effect of improved hip range of motion on maximum hip angle in pole vaulting: a pilot study - Enoki, S.; Kuramochi, R.; Nakayama, K.; Takigawa, H. (Asian Journal of Sports Medicine, 2023)
Background: Large maximum hip flexion and extension range of motion is considered effective in preventing injury in pole vaulters. Nonetheless, whether the improvement in hip flexion and extension range of motion changes their hip joint angle during pole vaulting remains unclear. Objectives: The present study aimed to clarify the acute effects of intervention for hip flexion and extension range of motion in pole vaulters on the maximum hip joint angle during pole vaulting. Methods: Seventeen male pole vaulters who underwent the same intervention for hip range of motion were included. The maximum hip joint angle during the pole vault from the touchdown of the last step of the run-up to the pole straightening was calculated from videos taken pre- and post-intervention and was subsequently compared. The pole vaulters cleared bungee bars that were set at the height of 90% of their personal best record. Three types of self-massages were used to improve the hip flexion and extension range of motion, and an active straight leg raise exercise was also performed. All intervention programs were completed in approximately 25 min on an experimental day, and all interventions were monitored by the examiner. Results: No significant improvements were observed between pre and post-intervention hip range of motion. The magnitude of change in the range of motion of active hip flexion was significantly correlated with the magnitude of change in the maximum hip flexion angle during pole vaulting pre-and post-intervention (P = 0.002, r = 0.687). Conclusions: Athletes should find ways to improve their active range of motion to prevent injuries and improve their performance. Coaches and athletic trainers should adopt an active range of motion as an indicator to control athlete conditioning.